Determination of Sea Boundaries from the Perspective of Regional Autonomy in Administrative Region of the Republic of Indonesia - Eka Djunarsjah (Jurnal Sosioteknologi, 2019)
Although the Djuanda Declaration had proclaimed on December 13th 1957, it was not until the administration of the Republic of Indonesia constitutes that the boundaries of the state were established through the Act (UU) in 2000. Despite several legislations related to the sea boundary, namely: Law on Continental Shelf of Indonesia (1973), Law on Exclusive Economic Zone of Indonesia (1983), and Law on Indonesian Waters (1996). The Indonesian administration, for the first time in 1999, decreed a Law on the Regional Government, which states the existence of regional authority in managing the sea area as far as 12 nautical miles from the coastline of each region. This contribution examines the extent of the relationship between the determinations of the boundary of the territorial waters of the Unitary State of the Republic of Indonesia (NKRI) based on the United Nations Convention of the Law of the Sea (UNCLOS) in 1982 with the determination of the regional sea boundary that refers to the Law on Regional Government. The method of study is a correlation analysis between laws and regulations related to state and regional sea boundaries. The results of the study indicate that the determination of the state sea boundary using baseline points (base points) refers to the position of the low water line; while for the sea boundary area the reference used is the coastline at the highest tide position. Another thing that is revealed, the integrity of NKRI sovereignty will be difficult to be realized if the determination of the sea border area of NKRI based on Regional Autonomy is not realized.